Atributos químicos do solo sob plantio direto afetado por sistemas de culturas e fontes de adubação - Costa, Mônica S. S. D. M.; Pivetta, Laércio A. [UNESP]; Steiner, Fábio [UNESP]; Costa, Luiz A.D.M.; Castoldi, Gustavo [UNESP]; Gobbi, Fernando Cesar (Revista Brasileira de Ciencias Agrarias, 2011)
Crop systems and fertilization sources can affect the chemical properties of the soil and, consequently, its fertility. With the aim of evaluating the effect of such management practices, soil samples collected at 0.0-0.10; 0.10-0.20; and 0.20-0.40 m in depth were collected and analyzed in the second year of an experiment installed in 2006 in a Rhodic Hapludox under no-till farming, located in the Agronomic Experimental Station of UNIOESTE, in the city of Marechal Candido Rondon, Parana, Brazil. The experiment consisted of two crop systems (with and without rotation of cover crops) and three fertilization sources (mineral, organic and mineral+organic). The organic and mineral+organic fertilizations consisted of the application of animal manure alone and animal manure mixed with mineral fertilizer, respectively. The values of pH, exchangeable potassium (K +) and cation exchange capacity (CEC) were not affected by the different crop systems, related to the application of different fertilization sources. However, they did influence the organic matter contents (OM), potential acidity (H + + Al 3+), exchangeable aluminum (Al 3+), phosphorus (P), calcium (Ca 2+), magnesium (Mg 2+), and the bases sum and saturation (V%). The organic and mineral+organic fertilizations, with animal manure promoted the highest increase in soil Ca and Mg.
Chemical attributes of soil under no-till farming affected by crop systems and fertilization sources
Keywords: Cover crops; Crop rotation; Fertilizer; Organic fertilization; Soil fertility; Animalia